Placental pathologic lesions associated with stroke in term neonates - Leon, Rachel L.; Kalvacherla, Vinay; Andrews, Michelle Machie; Thomas, Jennifer M.; Mir, Imran N.; Chalak, Lina F. (Frontiers in Endocrinology, 2022)
Objective: To determine the birth prevalence of perinatal stroke in term born infants at our high-volume delivery center and assess the frequency of both gross and histologic placental pathologies associated with perinatal stroke using the Amsterdam Placental Workshop Group Consensus Statement guidelines and definitions. Study Design: A single-center retrospective cohort study spanning 2010-2020. Results: There were 129,759 live births at Parkland Hospital during the study period and a total of 18 term born infants leading to a birth prevalence of 1 in 6,829 infants. Perinatal risk factors were found in all but one patient, and 74% presented with seizures. Pathologic placental examination was available in 56% of the cohort and only one patient had normal placental examination. Acute histologic chorioamnionitis was described in five placentas (50%) and an additional two had isolated umbilical and/or chorionic plate vasculitis with or without funisitis compared to a rate of 28% with acute inflammation in a Control group. Chronic inflammation in the form of villitis of unknown etiology was described in three of the acutely inflamed placentas and was high-grade in each of those while none of the placentas from our Control group showed evidence of any chronic lesion. Conclusion: Both acute and chronic placental inflammation are common in perinatal stroke; placental examination should be considered an essential component to the diagnostic workup.